1984
DOI: 10.1111/1523-1747.ep12262597
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Gamma Interferon Induces HLA-DR Expression on Cultured Human Keratinocytes

Abstract: In normal human epidermis, expression of HLA-DR antigen is restricted to Langerhans cells (LC) and acrosyringial epithelium. However, in diseases such as lichen planus and graft-vs.-host, HLA-DR antigen appears to be expressed by keratinocytes, although the exact source of the HLA-DR is unclear. Two possibilities are that (1) the HLA-DR is shed by neighboring immunocompetent cells, or (2) that the keratinocytes are synthesizing the antigen themselves. Recently, gamma interferon has been shown to induce HLA-DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
76
0

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 329 publications
(83 citation statements)
references
References 13 publications
6
76
0
Order By: Relevance
“…HLA-DR synthesis by keratinocytes has been demonstrated to be induced by interferon in vitro (5). The present study showed that occurrence of HLA-DR on keratinocytes was invariably linked to the presence of lymphocyte infiltrates, including T-lymphoma cells, which were also CD3-positive, HLA-DR-positive, predominantly CD4-positive and occasionally IL-2 receptor-positive, as previously reported by others (3,10).…”
Section: Discussionsupporting
confidence: 90%
“…HLA-DR synthesis by keratinocytes has been demonstrated to be induced by interferon in vitro (5). The present study showed that occurrence of HLA-DR on keratinocytes was invariably linked to the presence of lymphocyte infiltrates, including T-lymphoma cells, which were also CD3-positive, HLA-DR-positive, predominantly CD4-positive and occasionally IL-2 receptor-positive, as previously reported by others (3,10).…”
Section: Discussionsupporting
confidence: 90%
“…HLA-DP-reactive T cells administered at the time of SCT may result in both GVHD and GVL reactivity as a consequence of upregulated HLA-DP expression on non-hematopoietic cells caused by proinflammatory cytokines released as a consequence of tissue damage induced by the conditioning regimen or infections. 11,12 T-celldepleted SCT followed by the infusion of donor T cells at a later time point, however, may more selectively induce a GVL response when tissue damage is largely restored, and the expression of HLA-DP is anticipated to be restricted to hematopoietic cells. In this study we showed that resting FBs and most other non-hematopoietic cell lines did not express HLA-DP and were therefore not recognized by the T-cell clones.…”
Section: Discussionmentioning
confidence: 99%
“…However, HLA class II expression can be upregulated on various tissues after exposure to proinflammatory cytokines. 11,12 An anti-HLA class II immune response following HLA class II-mismatched SCT may therefore also result in GVHD if HLA class II molecules on nonhematopoietic tissues are upregulated as a consequence of the conditioning regimen or infections. 13 The results obtained from clinical transplantation studies concerning the impact of mismatching for different HLA alleles have led to the current standard that patient and donor are usually preferably matched for the HLA class II alleles HLA-DR and HLA-DQ in addition to the HLA class I molecules.…”
Section: Introductionmentioning
confidence: 99%
“…This correlation suggests that T cells are important in the generation of psoriatic plaques . IFN-y has been shown to induce HLA-DR expression by normal keratinocytes (35), as well as by other epithelial cells (36)(37)(38) . Recently (39), intradermal injection of recombinant IFNy into cutaneous lesions of patients with lepromatous leprosy has been shown to induce HLA-DR expression by keratinocytes.…”
Section: Discussionmentioning
confidence: 99%